PERFORMANCE ASSESSMENT OF SURFACE MINER IN INDIAN COAL MINES - Rahul Pandey, Dr. Rajni Kant; Shailendra Bommanwar (Journal of Computational Analysis and Applications (JoCAAA), 2024)
The increasing demand for coal in India has accelerated the adoption of advanced miningtechnologies. Surface miners are gaining importance as they eliminate drilling and blasting, reduce environmental impact,